2020
DOI: 10.1093/geroni/igaa057.982
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Cognitive Function, and Relations With Quality of Life and Psychological Distress

Abstract: Objective and subjective cognitive function have been associated with decreased quality of life and increased psychological distress in older adults. The present study examined relations of objective and subjective cognition with quality-of-life and mental-health outcomes in individuals with amnestic mild cognitive impairment (aMCI). The sample included 98 older adults with aMCI (92.5% male, age = 70.9±9.2 years). Measures included objective cognition (i.e., attention, memory, language, visuospatial abilities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In terms of quality of life, a study by Chandler et al reported a more significant effect of exercise (e.g., yoga) on memory-related quality of life compared to the support group (effect size = 0.43; 95% CI = 0.13 to 0.72) (31). The Nuzum et al study also confirmed that this effect was strongly associated with quality of life (r = −0.38, p < 0.01) (32). As confirmed by large-scale longitudinal studies, both depressed mood and poor quality of life can disrupt the normal lives of older adults with mild cognitive impairment and may further contribute to their cognitive decline (33)(34)(35).…”
Section: Discussionmentioning
confidence: 83%
“…In terms of quality of life, a study by Chandler et al reported a more significant effect of exercise (e.g., yoga) on memory-related quality of life compared to the support group (effect size = 0.43; 95% CI = 0.13 to 0.72) (31). The Nuzum et al study also confirmed that this effect was strongly associated with quality of life (r = −0.38, p < 0.01) (32). As confirmed by large-scale longitudinal studies, both depressed mood and poor quality of life can disrupt the normal lives of older adults with mild cognitive impairment and may further contribute to their cognitive decline (33)(34)(35).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, there was no apparent association between changes in self‐perceived cognitive functioning developed and changes in objective cognitive performance. This could suggest that self‐perceived and objective cognitive functioning are not two sides of the same coin, as they seem to reflect distinct processes 44 . It is also conceivable that characteristics we did not consider here may have influenced the relationship between subjective and objective cognitive performance.…”
Section: Discussionmentioning
confidence: 93%
“…This could suggest that self-perceived and objective cognitive functioning are not two sides of the same coin, as they seem to reflect distinct processes. 44 It is also conceivable that characteristics we did not consider here may have influenced the relationship between subjective and objective cognitive performance.…”
Section: Discussionmentioning
confidence: 99%